The Clinical Understaging of Recurrent Glottic Carcinoma after Radiation Failure - Moustafa Mourad; Sami P. Moubayed; Ilya Likhterov; Mark Urken (Case Reports in Otolaryngology)
Background. Recurrent glottic squamous cell carcinomas following radiation therapy for early staged tumors are oftentime early staged tumors. Management of these early stage recurrences presents a dilemma for the head and neck surgeon. Difficulties in appropriate tumor mapping, preoperative analysis, and poor understanding of the virulent pathologic nature of the recurrence may impede surgical decision-making. Methods. This is a single surgeon case report, presenting a patient with rapid recurrence following salvage transoral resection for an early stage recurrence, necessitating a total laryngectomy. Results. A review of the literature was performed, identifying studies that expound on the pathologic behavior of radiation recurrent disease. Conclusions. Radiation recurrent glottic squamous cell carcinoma has a distinct pathologic behavior and aggressive nature. Disease virulence, coupled with difficulty in appropriate staging and preoperative tumor mapping, should guide the surgeon when deciding the surgical management in the salvage setting.